Pharmacotherapy of Chronic Obstructive Pulmonary Disease: A Clinical Review. (12th March 2013) - Antus, Balazs
Abstract : Chronic obstructive pulmonary disease (COPD) is one of the leading causes of mortality and morbidity worldwide. In addition to generating high healthcare costs, COPD imposes a significant burden in terms of disability and impaired quality of life. Unlike many leading causes of death and disability, COPD is projected to increase in many regions of the world as the frequency of smoking is rising and the population is aging. The pharmacological treatment of COPD includes bronchodilators to relax smooth muscle, such as β 2 -agonists (salbutamol, terbutaline, and fenoterol, short-acting β 2 -agonists as well as salmeterol, formoterol, and indacaterol, and long-acting β 2 -agonists) and anticholinergics, such as ipratropium, oxitropium (short-acting anticholinergic), and tiotropium (long-acting anticholinergic). Although airway inflammation in COPD poorly responds to steroids, several inhaled corticosteroids (fluticasone, budesonide, and beclomethasone) are in use in combination with long-acting β 2 -agonists. Other medications include theophylline (both a bronchodilator and a phosphodiesterase inhibitor) and the phosphodiesterase-4 antagonists, such as roflumilast. Finally, a number of novel long-acting anticholinergics and β 2 -agonists with once- or twice-daily profiles are in development and clinical testing.